Maternal lipid profile during early pregnancy and birth weight: A retrospective study - Zhu, Si-Meng; Zhang, Han-Qiu; Li, Cheng; Zhang, Chen; Yu, Jia-Le; Wu, Yan-Ting; Huang, He-Feng (Frontiers in Endocrinology, 2022)
Introduction: Elevated maternal serum lipid concentrations have been related to an adverse intrauterine environment and lead to abnormal birth weight. Objective: In this study, we aimed to explore the association between maternal lipid profiles during early pregnancy and birth weight with stratified pre-pregnancy body mass index (BMI). Methods: This retrospective cohort study was based on a large population from two major maternity centers in Shanghai, China. We included 57,516 women with singleton live birth between January 2018 and October 2020. All of the enrolled women had fasting lipid concentrations measured in early pregnancy. The primary outcomes were birth weight and risks of adverse birth outcomes, including macrosomia, and large for gestational age (LGA), low birth weight (LBW) and small for gestational age (SGA). Results: Higher maternal concentrations of total cholesterol (TC), triglyceride (TG), and low-density cholesterol (LDL-c) in early pregnancy were associated with increased birth weight. Ln transformed TG and levels exhibited a positive association with LGA and macrosomia (OR = 1.33, 95% CI: 1.25,1.42 and OR = 1.37, 95% CI: 1.24, 1.52), and showed a negative relationship with SGA (OR = 0.73, 95% CI: 0.62, 0.85). High TG (>75th percentile, 1.67 mmol/L) group also showed higher risks of LGA and macrosomia (OR = 1.21, 95% CI: 1.15, 1.28 and OR = 1.20, 95% CI: 1.10, 1.31) and decreased prevalence of SGA (OR = 0.71, 95% CI: 0.61, 0.83). Moreover, significant combined effects of pre-pregnancy BMI and lipid profiles on LGA and macrosomia were identified. Conclusions: Elevated maternal lipid profiles in early pregnancy are associated with higher birth weight and increased risks of LGA and macrosomia. We propose that serum lipid profiles in early pregnancy and pre-pregnancy BMI could serve as screening indexes for high-risk women.